Driving progress in exhaled breath biomarkers: Breath Biopsy Conference 2019. (13th July 2020) - Lawson, Jonathan; Boyle, Billy; Beauchamp, Jonathan
Abstract: November 2019 saw Cambridge, UK play host to the second Breath Biopsy Conference, a community-focused event aimed at sharing and supporting advancements in the collection and analysis of volatile organic compounds in exhaled breath. The event expanded upon the previous year's format, spanning two days and concluding with an expert panel discussion. Presentations covered detection, monitoring and precision medicine studies examining diseases including asthma, cirrhosis, cancer and tuberculosis. The meeting attracted representatives from diverse backgrounds, such as metabolomics, artificial intelligence, clinical research and chemical analysis. This meeting report offers an overview of what was presented and discussed during the conference.